Stable isotope ratios in a firn core from the east antarctic ice sheet Razões de isótopos estáveis em um testemunho de firn do manto de gelo da antártica oriental - Tavares, Flavia A.; Simões, Jefferson C.; Bernardo, Ronaldo T.; Gerhard, Nicoli P.; Casassa, Gino; Marquetto, Luciano (My University, 2020)
The 41.82 m deep firn core IC-02 (88°01'21.3"S and 82°04'21.7"W) was drilled in the East Antarctic ice sheet during a Chilean-Brazilian scientific traverse in the Austral summer of 2004/2005. This study aimed to determine the stable water isotopes (ẟ18O e ẟ D) and the snow annual accumulation annual rate. The core was subsampled in a continuous fusion system and the isotopic content determined by a ring-down resonant cavity laser spectrometry (WS-CRDS, Picarro system). The ẟ18O series ranges from-50.77 ‰ to-41.40 ‰ (mean-46.39 ± 1.37‰), while the ẟD ranges from-408.18 ‰ to -323.85 ‰ (mean-367.43 ± 12.51‰). The excess of deuterium (d) has an average of 4.36 ± 2.66‰. The core represents 85 ± 3 years of snow accumulation, that is, an average rate of 152 ± 64 mm year-1 in water equivalent. From the 1990s onwards, there was a decrease in the mean annual ẟD concomitant with an increase in the snow accumulation rate (17% from 1974 to 2003). The increase in this accumulation could be associated with a greater mobilization of drift snow to the deposition site, associated with a greater advection of oceanic air masses coming from the Antarctic seas (Amundsen, Bellingshausen, Weddell and Lazarev). Such interpretation is supported by the increase in the zonal winds velocity, as observed in anomalies fields of geopotential height, zonal wind and temperature at 500 mb in the NCEP / NCAR reanalysis.
Keywords: antarctica; firn core; stable isotopes